Analisis Kejahatan Terhadap Badan Dan Nyawa: (Studi Kasus Samin Pembunuh Satu Keluarga Di Serang, Banten) - Ciek Julyati Hisyam; Aline Nikita; Ekapatriani Paparesi; Fairuz Dhiya Putri; Ghifari Shafa Darmawan; Nadila Sahla Mulia; Selvy Gita Cahyani; Sifah Fauziah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
In social life, rules or norms act as social control to set the limits of society's behavior. In sociology, deviant behavior by individuals can be seen in a variety of factors that focus on social factors or circumstances around individuals. This article focuses on crimes against body and life with a case study of the murder of one family in the attack, Banten carried out by Samin. The research method used is a qualitative approach with descriptive methods used in this study by conducting analysis of documents obtained from various sources, such as journals, books, the Internet, and so on.